The Comparıson Of The Frontal Sınus Area Wıth Cephalometrıc Measurements In Anomalous Groups - Jalan Kama; Mehmet Ali Yeşil; Orhan Hamamcı (Galenos Yayinevi, 1998)
The aim of this study is to evaluate the correlation between the area (mm2) of the frontal sinus and cephalometric measurements. The samples included 90 patients with Angle CI I, CI II and CI III malocclusions who applied to Department of Orthodontics. Each group was divided into three subgroups: prepuberty, puberty and postpuberty, and the subgroups included 10 patients. The surface areas of the frontal sinuses were assessed by a digital planimeter on the lateral cephalograms, and their comparisons with cephalometric measurements were analyzed by correlation analysis. The surface area of the frontal sinus increased proportionally with age. There was a positive correlation between frontal sinus area and ANB angle in Class I and Class II groups of all Görevlisi growth periods and a negative correlation in Class III group of all growth periods. The amount and direction of growth and development are very important if the functional orthopedic therapy is thought. Although there are many methods on growth prediction of individual, the results are uncertain. Thus, we evaluated the correlation between the area of the frontal sinus and mandibular growth in our study. As a result of this study, it has been found that frontal sinus area increases with age and relates with mandibular growth.